2010
DOI: 10.1590/s1808-86942010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicidade por organofosforados: descrição dos aspectos ultraestruturais do sistema vestibulococlear de cobaias

Abstract: Organophosphat e toxic agents are used in agriculture and are currently part of the group of toxic agents which can lead to hearing loss, in which we have solvents, metals and asphyxiation agents. Aim: to analyze the acute ototoxic action of a group of organophosphate agents in the vestibulocochlear system. This is a prospective experimental study. Materials and Methods: we used male albino guinea pigs, broken down into three groups, to which we provided distilled water (group 1 -control), agrotoxic agent -0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…This result shows that a morphological change may suggest a functional disorder 25 . However, in the present study, there has been no manifestation of functional symptoms, and this may have been due to difference of the active ingredient tested, although it was an organophosphorus compound.…”
Section: Acknowledgmentsmentioning
confidence: 68%
“…This result shows that a morphological change may suggest a functional disorder 25 . However, in the present study, there has been no manifestation of functional symptoms, and this may have been due to difference of the active ingredient tested, although it was an organophosphorus compound.…”
Section: Acknowledgmentsmentioning
confidence: 68%
“…This fact is probably related to male farmers be considered culturally more resistant to hard work, and also to be (Table 2). Regarding duration of time, studies reported the incorrect use of IPD associated to noise equipment may lead to hearing loss development in approximate four years 9,19 . These findings are important but were not confirmed in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients are extremely difficult to identify the cause of hearing loss, because there is a summation of causes 4 . Besides, the time to clinical condition to be installed, when is not due to acute intoxication, is gradual and long, approximated four years 9,19 . Other researches 9,26,27 already pointed out the need to control and guidance about the use of pesticides and the danger of noise exposition, promoting the knowledge and alarming the farmers about the hearing risks and the damage to health caused by farming activity without proper care and the individual protection devices used correctly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Letícia Regina Kunst (1) , Michele Vargas Garcia (1) , Alencar Kolinski Machado (1) , Fernanda Barbisan (1) , Aron Ferreira da Silveira (2) (1) Universidade Federal de Santa Maria -UFSM, Santa Maria, RS, Brasil.…”
Section: Sistema Olivococlear Medial E Genotoxicidade Em Escolares Deunclassified